Introducing English pronunciation : a teacher's guide to Tree or three? and Ship or sheep? - Baker, Ann. (Cambridge ; New York : Cambridge University Press, 1982)
This book is about: Teaching Pronunciation in the earley stages of EFL/ESL learning; Detailed teacher's notes; Diagnostic tests; and List of likely Errors.
Keywords: English language; Pronunciation; English language -- Textbooks for foreign speakers; English language -- Pronunciation